An examination of how patient and public involvement is used and valued in the clinical research approval process. - Hood, Ben; Bojke, Andy; Cooper, Catherine; Curtis, Lesley; Sellers, Sharon; Cruickshank, William (British Journal of Nursing, 2026)
Clinical research is crucial in enhancing patient care and developing new treatments in all healthcare settings. Patient and public involvement (PPI) is an essential element of the clinical research process that ensures patients and members of the public are involved in the design and delivery of any research. This article examines data collected from the DANIELLE study, a research project that aimed to review how PPI is currently used and valued within clinical research in the UK, with the aim of creating proposals for improving how PPI is employed in the future. The initial concept for this research was developed in response to the PPI group's experiences of reviewing clinical research studies over a 10-year period. The objective of this research was to explore the lived experiences of members of a cancer PPI group. Semi-structured interviews were used to examine the lived experience of PPI group members. Findings from this study suggest researchers need a stronger set of terms of reference for how they act and engage with PPI groups. PPI is promoted as being essential to the research approval process, however, this study raises questions around the legitimacy of how researchers use PPI feedback, and the legitimacy of how it is verified within current research approval process.